Perbandingan Kinerja Keuangan Berdasarkan Rasio Likuiditas, Solvabilitas, dan Profitabilitas pada Perusahaan : (Sub Sektor Pakan Ternak yang Terdaftar di BEI Tahun 2018–2023) - Rika Ayu Dwi Anggara; Ahmad Idris; Trisnia Widuri (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the comparison of financial performance based on the liquidity, solvency, and profitability ratios of animal feed sub-sector companies listed on the IDX in 2018-2023. This study uses comparative research and is included in quantitative research. The sampling technique was carried out using the Purposive Sampling technique. The results of this study indicate a significant difference in the financial performance of animal feed sub-sector companies listed on the IDX with stock codes CPIN, CPRO, JPFA, MAIN, and SIPD based on the liquidity ratio (CR), solvency (DER), and profitability (ROA). The results of this study are expected to provide a reference for related companies to improve their respective financial performance, especially for those whose values ​​are below or above the industry average and can be used as a consideration for prospective investors.